Standarisasi Parameter Spesifik dan Non-Spesifik Ekstrak Rimpang Lengkuas Merah (Alpinia Purpurata K. Schum) sebagai Obat Antibakteri - Fatimawali, .; Kepel, Billy J.; Bodhi, Widdhi (e-Biomedik, 2020)
Abstract: Red galangal rhizome (Alpinia purpurata K. Schum) has antibacterial activity categorized as very strong, therefore, it needs to be standardized. This study was aimed to standardize the ethanol extract of red galangal rhizomes obtained from plantations in North Minahasa region. Standardized extract had two parameters namely specific parameters and non-specific parameters. Determination of specific parameters includes extract identity, organoleptic test, levels of compounds that dissolve in water and that are soluble in ethanol, content test of alkaloids, flavonoids, saponins, and tannins. Meanwhile, non-specific parameters include drying losses, microbial contamination, total ash content, acid insoluble ash content, as well as Cd and Pb metal contamination. The results showed that red galangal rhizome extract had dark red-brown color, specific odor of galangal, slightly bitter taste, water soluble was 12.55%, and ethanol soluble was 8.25%. Its fitochemical contents were alkaloids, saponins, tannins, and flavonoids. Moreover, drying shrinkage of 19.17%, microbial contamination of 2.1 x 102 CFU /g, ash content of 0.36%, acid insoluble ash content of 0.36%, and Cd and Pb 0.062 and 0.091 ppm. In conclusion, based on standardization testing including specific and non-specific parameters, red galangal extract can meet the standardization of raw material quality.Keywords: Alpinia purpurata K. Schum, rhizome, standardizationÂ Abstrak: Lengkuas merah (Alpinia purpurata K. Schum) memiliki aktivitas antibakteri dengan kategori yang sangat kuat dan karenanya perlu distandarisasi. Penelitian ini bertujuan untuk menstandarisasi ekstrak etanol rimpang lengkuas merah yang diperoleh dari perkebunan di wilayah Minahasa Utara. Ekstrak standar dengan dua parameter yaitu parameter spesifik dan parameter non-spesifik. Penentuan parameter spesifik meliputi: identitas ekstrak, uji organoleptik, kadar senyawa yang larut dalam air dan yang larut dalam etanol, kadar uji alkaloid, flavonoid, saponin, dan tanin. Parameter non-spesifik meliputi: susut pengeringan, kontaminasi mikroba, kadar abu total, kadar abu tidak larut asam, kontaminasi logam Cd dan Pb. Hasil penelitian menunjukkan bahwa ekstrak rimpang lengkuas merah berwarna merah-coklat pekat, bau khas lengkuas, rasa agak pahit, larut dalam air 12,55%, dan larut dalam etanol 8,25%. Senyawa fitokimia yang terkandung ialah alkaloid, saponin, tanin, dan flavonoid. Susut pengeringan 19,17%, kontaminasi mikroba 2,1 x 102 CFU/g, kadar abu 0,36%, kadar abu tidak larut asam 0,36%, Cd dan Pb 0,062 dan 0,091 ppm. Simpulan penelitian ini ialah berdasarkan pengujian standardisasi termasuk parameter spesifik dan non-spesifik, ekstrak lengkuas merah memenuhi standar kualitas bahan baku.Kata kunci: Alpinia purpurata K. Schum, rimpang lengkuas merah, standarisasi